2016
DOI: 10.1177/0907568216649104
|View full text |Cite
|
Sign up to set email alerts
|

Belonging and participation in liminality: Unaccompanied children in Finland and Sweden

Abstract: This article investigates children’s participation and sense of belonging from the perspective of unaccompanied children, based on two qualitative research projects with unaccompanied children in Sweden and Finland. The results show that the unaccompanied children’s own understanding of their participation and belonging in different positions was fluid; for instance, the borders between childhood and adulthood, and striving for independence or wanting to be cared for by adults were flexible, allowing the child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 22 publications
(29 reference statements)
1
48
0
Order By: Relevance
“…The difficulty arises from several issues such as a lack of knowledge about and social trust towards foreign-looking young people. Sometimes even adults in the new host society might be suspicious about the motives of these young people (Gustafsson, Fioretosand, and Norström 2012;Kaukko and Wernesjö 2017). Ni Raghallaigh (2014, 91-92) describes this 'climate of mistrust' as one of the key factors hindering the minors from gaining trust in social relations and in society at large.…”
Section: Approaches To Identity Agency and Belongingmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty arises from several issues such as a lack of knowledge about and social trust towards foreign-looking young people. Sometimes even adults in the new host society might be suspicious about the motives of these young people (Gustafsson, Fioretosand, and Norström 2012;Kaukko and Wernesjö 2017). Ni Raghallaigh (2014, 91-92) describes this 'climate of mistrust' as one of the key factors hindering the minors from gaining trust in social relations and in society at large.…”
Section: Approaches To Identity Agency and Belongingmentioning
confidence: 99%
“…These young people have a limited possibility to live like other young people, since they are overwhelmed by the experiences of fleeing from home, journeying and the asylum process in the new host country. Their experiences of uncertainty are further amplified when they meet with institutional mistrust or there is a lack of trustworthy adults in their daily social environment (Kuusisto-Arponen 2015, 2016a; see also Björklund 2015;Herz and Lalander 2017;Kaukko and Wernesjö 2017;Kohli 2011). Whereas new psychosocial interventions are currently being developed to help children and young people with trauma memories (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We have noticed similar tendencies in our project. We have found that these are often related to experiences among the young migrants living in municipal and private facilities of being treated, by staff members, like children who fail to accommodate to a desired 'Swedishness' (Kaukko & Wernesjö 2016;Lalander & Raoof 2017). Such experiences create problems in communication and trust, resulting in a situation where residents provide staff members with 'thin' narratives (Kohli 2006) and reinforce staff-resident boundaries.…”
Section: Methodsmentioning
confidence: 93%
“…This includes studies on their placement in foster care (Sirriyeh, 2013;Bates et al, 2005) and in residential care (e.g. Kaukko & Wernesjö, 2017;Söderqvist, Sjöblom, & Bülow, 2016), as well as in care and protection institutions in the context of (forced) re-migration and deportation (e.g. Thompson, Torres, Swanson, Blue, & Hernández Hernández, 2019;Dietrich, 2015;Robinson & Williams, 2015).…”
Section: Research On How Urms Experience Social Relationships: Researmentioning
confidence: 99%